Analisis Faktor-Faktor Yang Mempengaruhi Fungsi Intermediasi Serta Dampaknya Terhadap Kinerja Keuangan BUS Di Indonesia - Ridho Fikri Almi; Roikhan Mochamad Aziz (ITB AAS INDONESIA Surakarta, 2023)
The current problem is a decline in the intermediation function of Islamic commercial banks (BUS), which is reflected in the FDR ratio. The purpose of this study is to determine the factors that affect the intermediation function of tangible assets and intangible assets that exist in the BUS and how the impact on the financial performance of the BUS. The study was conducted on 8 BUS. This research method uses path analysis with trimming model. The results of the study state that partially TPF, NPF, CAR have an effect on FDR, partially there is no significant effect between BOPO and iB-VAICTM on FDR. Partially there is a significant effect between TPF, NPF, CAR, iB-VAICTM and FDR on ROA and partially there is no significant effect between BOPO on ROA. Simultaneously there is the influence of TPF, NPF, CAR, BOPO, and iB-VAICTM there is an intermediation function proxied by FDR and simultaneously there is the effect of TPF, NPF, CAR, BOPO, iB-VAICTM and FDR on the financial performance of Islamic commercial banks proxied with ROA. This study is expected to be used as an evaluation material for the decline in the intermediation function in the BUS. BUS is expected to optimize the promotion of services/products, in order to increase public inclusion of Islamic banks and also increase the capacity of human resources in banking (intangible assets), conduct call center training, and recruit quality human resources